METODE PENANAMAN NILAI-NILAI AQIDAH PADA SISWA SD ALAM MUHAMMADIYAH BANJARBARU - Hendra Hendra; Nurul Qomariyah (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2018)
The focus of the research is how method teachers in instilling the values of aqidah in elementary school students Nature Muhammadiyah Banjarbaru and contributing factors that affected it. Whereas the purpose of this research is to know the methods of teachers in instilling the values of aqidah in elementary school students Nature Muhammadiyah Banjarbaru and contributing factors that affected it. This type of research is a field of research field research using a qualitative approach. The subject of this research is a first-grade teacher and teacher of Islamic education in primary school Muhammadiyah Banjarbaru, while Natural objects in this research are the cultivation of the values of aqidah in elementary school students Nature Muhammadiyah Banjarbaru. The results showed that the method of planting on faith values students Natural Muhammadiyah already on aim teachers through example, practice methods, exercises, stories, and singing was already good. It is seen from the way the teacher in everyday life they provide an example like say thoyyibah sentence, giving the Islamic story so taken their example as well as train and familiarize activities e.g., days are like reading the Qur'an, dhuha prayer, Zuhr and ' ASR prayers congregation. As for the factors that influence the cultivation of the values of faith in Natural place of Muhammadiyah students to include: (1) family environment; the family environment is the most effect on the cultivation of the values of faith in children. Parents play a role as the person who first gave the education of aqidah. (2) the school environment; the influence of the natural environment of ELEMENTARY SCHOOL Muhammadiyah in the cultivation of the values against their students in aqidah categories are. A comfortable natural environment school and shady atmosphere making learning more convenient and not boring. Written and implemented activities e.g. school day aims to shape the character of the work of students, have aqidah and noble character. (3) the environmental community; the influence of the environment of the community against the cultivation of the values of faith in students of ELEMENTARY SCHOOL Nature of Muhammadiyah in category enough. It is seen from the student's activities outside the school environment or when returned home. Keywords: Education, Methods, Aqeedah, Islamic Values.